The Realization of Grice’s Maxims in English Teacher’s Interaction with Male and Female Students - Khayati, Iftitah; Mujiyanto, Januarius; Warsono, Warsono (English Education Journal, 2019)
Grice’s maxims refer to the use of the four conversational implicature and cooperative principle proposed by Paul Herbert Grice (1975). In order to make communication successful, participants have to follow such a principle. This study is aimed at investigating the realization of Grice’s maxims in English teacher’s interaction with male and female students at Bilingual Boarding School and the gender difference that influenced the interaction. The researcher uses descriptive qualitative in analyzing the data. The main instrument used was the researcher herself with the help of the data sheet as the secondary instrument. The object of the study was the teacher’s interaction with male and female students in a different classroom. Then, the data were analyzed in four steps of interactive analysis: data collection, data reduction, data presentation, and data conclusion. To avoid bias or subjectivity, the researcher applied the triangulation of expert judgment. The results show that all the four Grice’s maxims, quality, quantity, relevant, and manner are realized in the teacher’s interaction with male and female students. It was realize by observing and flouting the maxims. In the interaction with male students, there are 4 observances of Grice’s maxims realized they are observed quality maxim, quantity maxim, relevant maxim, and manner maxim. In non-observance of maxims, there are flouted quality, quantity, relevant and manner maxims. On the other hand, the realization of Grice’s maxims in the interaction with male students was observed the quality, quantity, relevant, manner and flouted 2 maxims were quantity and relevant maxim. The results of this study can pedagogically contribute to English language studies. In the classroom interaction in discourse and pragmatic development in general, the realization of maxims (observed and flouted) can be directly included as a good example of the natural authentic of English.